Revision of Metaconchoecia (Ostracoda: Halocyprididae) and the designation of two new tribes Conchoeciini and Metaconchoeciini - Chavtur, Vladimir G.; Angel, Martin V. (Zootaxa, 2011)
A new tribe of pelagic Ostracoda (Halocyprididae), the Metaconchoeciini, is established to encompass all the species formerly classified in the genus Metaconchoecia. All the remaining genera in the subfamily Conchoecinae are, therefore, assigned to another new tribe, the Conchoeciini. The original genus Metaconchoecia is subdivided into ten genera. Metaconchoecia is retained and nine new genera established namely: Austrinoecia, Clausoecia, Deeveyoecia, Juryoecia, Kyrtoecia, Muelleroecia, Nasoecia, Rotundoecia and Vityazoecia. Keys to these new genera and their component species are provided. Tables summarize the characters that most readily distinguish between the most closely related taxa. Appendices summarize the taxonomic characters and detailed size data for the majority of species that occur in the Atlantic and the North Pacific. A new species, Vityazoecia distoglandula, is described, which is designated as the type species of its genus.